Efficacy of Pythium oligandrum on improvement of lucerne yield, root development and disease score under field conditions - Pisarčik, Martin; Hakl, Josef; Szabó, Ondřej; Nerušil, Pavel (Frontiers in Plant Science, 2022)
Introduction Biological control of root diseases of lucerne (Medicago sativa L.) has potential benefits for stand performance but this remains unsupported by evidence from practical field studies. Methods In field experiments at three sites our objectives were to determine the effect of Pythium oligandrum, as spring, autumn and intensive regime treatments on (i) lucerne plant density and root traits development, and (ii) forage yield and forage traits. Lucerne stands were managed under two or three treatments: non-treated control and P. oligandrum applied at two intensities of application under four-cut utilization. Results and discussion Under relatively dry conditions (annual mean 10°C and <500 mm precipitation) lucerne dry matter yield was significantly reduced by 6%, which could be related to mechanisms of inappropriate stimulation and disturbance of the balance between auxins and ethylene. Under annual precipitation of >500 mm, positive impacts on stand height or fine root mass were observed for the autumn and intensive treatments where positive root response was visible only in alluvial soil. However, these changes did not result in higher yield and probably more applications per year will be needed for significant forage yield improvement. This study highlights the limits of field-scale biological control in which the potential of P. oligandrum for lucerne productivity improvement was realised only under a humid environment or deep alluvial soils, where higher root disease infestation may also be expected.